超临界/超超临界火电机组齿轮调速传动装置研究与应用 - 孟令先; 刘忠明; 张志宏; 李纪强; 张和平; 王振; 王征兵 (Jixie chuandong)
The characteristics,research and application of the gear speed adjusting transmission device for supercritical /Ultra-supercritical thermal power units is summarized.The key technology of the domestic gear speed adjusting transmission device is need to conquer.The development prospects of large gear speed adjusting transmission device is forecasted.